Optical Fiber Communication Conference 2012
DOI: 10.1364/ofc.2012.om3g.6
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of GMPLS-Controlled Device Power Management for Next Generation Green Optical Networks

Abstract: Abstract:We propose GMPLS protocol enhancements enabling dynamic power state management of optoelectronic network devices for setup-time-aware differentiated connection provisioning. Daily energy savings of 56% are demonstrated in a Pan-European-like network compared to always on scenarios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…With the aim of saving energy, the HALF‐MOON project proposed the dynamic power management of OE devices (i.e., transponders (TSPs) and regenerators (REGs)) [32]. OE devices can be totally or partially powered (“up” and “idle” states, respectively) or switched‐off (“down” state).…”
Section: Half‐moon Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…With the aim of saving energy, the HALF‐MOON project proposed the dynamic power management of OE devices (i.e., transponders (TSPs) and regenerators (REGs)) [32]. OE devices can be totally or partially powered (“up” and “idle” states, respectively) or switched‐off (“down” state).…”
Section: Half‐moon Approachmentioning
confidence: 99%
“…In the scenario considering 1:1 protection, if OESM is implemented, TSPs/REGs allocated for backup paths can be set in idle‐state to save energy when inactive, while still ensuring fast response times in case of failure (i.e., gold class setup times average ∼10 milliseconds [32]). Regarding amplifier sites, however, even if they could be woken‐up in tens or hundreds of milliseconds, long‐haul links easily comprise many which have to be sequentially activated.…”
Section: Half‐moon Approach For Energy Savings: a Case Studymentioning
confidence: 99%
“…[5], [6]) confirm the benefits of putting some elements in core optical networks into a low-power consumption mode. In [7], different classes of traffic are considered and, as a consequence, the setup time of the connections becomes a critical parameter, since typically high-priority traffic (e.g., real-time traffic) requires short set-up times, while low-priority traffic does not. Considering that the boot-up time (i.e., the time required for the transition of a TSP or a REG from the off to on mode) can be quite long (tens of seconds [4]), available TSPs and REGs in the off mode cannot be allocated to support highpriority traffic.…”
Section: Introductionmentioning
confidence: 99%
“…1 depicts the inter-state transitions. Let us now consider the case of different classes of connections [3]. In this context, the set-up time requirements of the connections might become a critical parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Note that, by reserving some of the available TSPs per node for C h traffic and putting them on IDLE state, it is possible to satisfy both C h and C l connections set-up time requirements, and, at the same time reduce the power consumption of the network. For instance, authors in [3] reported daily power savings around 56% with respect to traditional WDM network scenarios. However, besides the power savings, we must carefully evaluate the impact of this power management strategy on the blocking of the connections, e.g., due to the lack of available TSPs, specifically, lack of IDLE TSPs for C h traffic and lack of OFF TSPs for C l traffic.…”
Section: Introductionmentioning
confidence: 99%